CHINESE SOCIAL CREDIT SYSTEM: NEW CHALLENGES FOR THE RIGHT TO PRIVACY? - Sinisa Domazet (Institute for Research and European Studies, 2021)
The Social Credit system (SCS) in China is being applied in an increasing number of areas of everyday life. This system is built around rewarding and punishing specific forms of social behavior. The question arises whether this system is a new challenge to the right to privacy. The study, which is supported by literature, sheds light on how novel this thought is. This paper uses the comparative method, normative method, and legal-logical methods of induction and deduction. According to the research, the SCS in basic is a state project. The key distinctions between the SCS and similar systems in Western countries include the impact on individuals, state dependency, punitive policy, the breadth of consequences, and cultural differences. In addition, one of the tools of the SCS in China is ‘shame’, which is focused on maintaining harmonious relations within a society. In the West, the focus is more on the citizens’ rights.